Response of five legume cover crops to phosphoric fertilization - Gómez Gómez, Robin; González Lutz, María Isabel (Agronomía Mesoamericana, 2018)
Legume cover crops are planted to control weed, to prevent soil erosion, and to increase nitrogen in soil. The objective of this study was to evaluate the response to phosphorus fertilization of the legumes Mucuna pruriens cv. cinza, Mucuna pruriens cv. preta, Crotalaria spectabilis, Vigna radiata, and Pueraria phaseoloides, during two seasons of the year. The experiment was carried out in a greenhouse at the Agricultural Experiment Station Fabio Baudrit Moreno (EEAFBM, in Spanish), of the University of Costa Rica, Alajuela, Costa Rica, from November 2012 to January 2013, and it was replicated from April to May 2013. Doses of 0, 30, 60, and 90 kg P2O5/ha were applied on steam sterilized soil, and then it was used to fill 2 kg capacity pots. The variables assessed were plant height, a number of true leaves, and dry weight 18-26 days after planting depending on legume species. Crotalaria spectabilis, V. radiata, and P. phaseoloides achieved the highest growth when fertilized at the rate of 60 kg P2O5/ha, whereas both M.prurienscultivars did not increase growth as a response to phosphoric fertilization. Due to the positive effect of phosphorus fertilization on growth of small-seeded legumes, it is important to validate the use of this fertilizer to achieve rapid soil cover, which could decrease weed competition.